2017
DOI: 10.1097/md.0000000000008965
|View full text |Cite
|
Sign up to set email alerts
|

bla OXA-23-like and bla TEM rather than bla OXA-51-like contributed to a high level of carbapenem resistance in Acinetobacter baumannii strains from a teaching hospital in Xi’an, China

Abstract: Acinetobacter baumannii is one of the major threats in clinical infections due to its antibiotic resistance ability. It shows increasing resistance to carbapenems, mainly due to β-lactamase mediated mechanisms. The aim of this study was to investigate carbapenem resistance (CR) profiles and analyze β-lactamases genes composition of clinical A. baumannii strains from a teaching hospital in Xi’an. The resistance patterns to imipenem and meropenem were checked for 51 clinical A. baumannii strains. The existence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Only A. baumannii MK60, MK22, O3, and A2 lack the bla OXA-23-like gene. The presence of this gene has been reported as having the strongest correlation with high resistance levels against carbapenems such as meropenem and imipenem (20). Accordingly, strains O3 and A2, which lack the bla OXA-23-like gene, are susceptible to meropenem and imipenem.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only A. baumannii MK60, MK22, O3, and A2 lack the bla OXA-23-like gene. The presence of this gene has been reported as having the strongest correlation with high resistance levels against carbapenems such as meropenem and imipenem (20). Accordingly, strains O3 and A2, which lack the bla OXA-23-like gene, are susceptible to meropenem and imipenem.…”
Section: Resultsmentioning
confidence: 99%
“…Exponentially grown bacterial cells were suspended in high tonicity, corresponding to a low intracellular turgor pressure (20 mM HEPES-NaOH, 150 mM NaCl [pH 7.4]) and then treated with 500 g/ml LysMK34 for 2 h at room temperature. The treated cells were washed twice using high-tonicity buffer and then either diluted prior to plating in high-tonicity (20 turgor pressure. Thus, also under conditions of low intracellular turgor pressure, LysMK34 can penetrate the outer membrane and then reach the peptidoglycan layer.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yang et al collected 2,197 A. baumannii isolates from 27 provinces in China, found that the resistance rate for cefoperazone-sulbactam was 39.7%, and demonstrated that bla TEM−1 with four tandem copies structure played a key role in this resistance phenomenon (18). Meanwhile, Han et al proved that bla OXA−23 and bla TEM−1 genes were more conducive to resistance to carbapenems in A. baumannii (19). In the current study, bla TEM−1 gene had been detected in all isolates since 2012, and the overall positive rate of this resistance gene was 75.3% (222/295), meanwhile, the cefoperazone-sulbactam resistance rate of the 295 MDR A. baumannii isolates was up to 94.5%, and both had a certain correlation relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the 2015 SMART surveillance program, involving 17 European countries, revealed that the overall susceptibility of A. baumannii to imipenem was only 10.1% 27 and somewhat lower than found in the present study (21.0%). However, in both studies the imipenem non-susceptibilities could not be restored by relebactam in imipenem non-susceptible A. baumannii isolates, which has also been reported in the USA 15 and has been attributed to certain resistance mechanisms of A. baumannii strains, 28,29 since a main mechanism of carbapenem resistance in A. baumannii is expression of OXAs. 30 The A. baumannii percent susceptibilities to imipenem and imipenem/relebactam were virtually identical (both about 20%), whereas for amikacin they were 16.5-32.7%, indicating amikacin resistance, which has been attributed to aminoglycoside-modifying enzyme expressions in A. baumannii.…”
Section: General Distribution Of P Aeruginosa and A Baumannii From 2015 To 2018mentioning
confidence: 54%